Reverenz an die Referenz - Panagl, Oswald (Muzikološki zbornik, 2013)
Firstly, the paper addresses a number of linguistic interpretations of the term "reference" in the fields of semantics and philosophy of language. It is differentiated between extension and intension as well as referred to the meaning of the concept in the frame of the speech act theory. Another chapter discusses numerous interpretations of "reference" in the modern spectrum of linguistic disciplines. In conclusion the paper investigates the linguistic processes and their application in the musicological problem areas.
Keywords: jezikovna filozofija; metadisciplinarnost; semantics; semantika